Women's Health Choices and the Effects on Child Health - Therése Hindman Persson (Lund University, School of Economics and Management, Department of Economics, 2001)
This paper analyses, both theoretically and empirically, women's health choices and their effects on child health for a sample of rural households in Cebu, Philippines. The present study differs from other studies by analysing separately prenatal and postnatal determinants of child health both under certainty and uncertainty, hence introducing the possibility of different health production functions before and after birth. An approach that is well in line with recent research in nutrition and epidemiology. Theoretically, the model predicts that the larger the probability of survival the less is spent on child specific health inputs after birth. That is, the less money need to be spent on compensating the child for a "bad start" in life. Empirically, the results show that family specific health endowments may explain a large part of the child's health, that water and sanitation are important for child health, and that smoking has a significant and negative effect on the health of the child after birth.
Keywords: I12; I31; O15; 330; Philippines; Child Health; Health Production Function; Uncertainty; Water and Sanitation